Infestation of Luke Worm (Fasciola sp) and Stomach Worm (Paramphistomum sp) on Adult Bali Cattle in Tenayan Raya Pekanbaru Municipality - Fahrur Rozi; Jully Handoko; Rahmi Febriyanti (Fakultas Kedokteran Hewan Universitas Gadjah Mada bekerjasama dengan PB PDHI, 2015)
This study was conducted at the Laboratory of Parasitology, Veterinary Investigation Center Regional II,Bukittinggi in January until February 2013. Bovine fecal samples of Bali cattle were taken in the District of Tenayan Raya Pekanbaru Municipality. This study was aimed to determine the prevalence of paramphistomiasis and fascioliasis of adult males and females Bali cattle and the number of eggs worm per gram of feces as well. A total of 232 fecal samples were tested by Parfit and Banks, and McMaster. Results showed that the prevalence of Fasciola spp. in males Bali cattle and cows was 49.02% and 60.71%, respectively, whereas the prevalence of Paramphistomum spp. in males Bali cattle and cows was 46.07% and 50.00%,respectively. Result count of the average number of worm eggs using Mcmaster in the fecal samples of Bali cattle in males and females was 205.88 eggs/g and 267.85 eggs/g, respectively. This study indicated that the eggs worm counts per gram feces could be classified into mild infection.